Recent Review on Biological Barriers and Host-Material Interfaces in Precision Drug Delivery: Advancement in Biomaterial Engineering for Better Treatment Therapies - Rohitas Deshmukh; Pranshul Sethi; Bhupendra Singh; Jailani Shiekmydeen; Sagar Salave; Ravish J. Patel; Nemat Ali; Summya Rashid; Gehan M. Elossaily; Arun Kumar (MDPI AG, 2024)
Preclinical and clinical studies have demonstrated that precision therapy has a broad variety of treatment applications, making it an interesting research topic with exciting potential in numerous sectors. However, major obstacles, such as inefficient and unsafe delivery systems and severe side effects, have impeded the widespread use of precision medicine. The purpose of drug delivery systems (DDSs) is to regulate the time and place of drug release and action. They aid in enhancing the equilibrium between medicinal efficacy on target and hazardous side effects off target. One promising approach is biomaterial-assisted biotherapy, which takes advantage of biomaterials' special capabilities, such as high biocompatibility and bioactive characteristics. When administered via different routes, drug molecules deal with biological barriers; DDSs help them overcome these hurdles. With their adaptable features and ample packing capacity, biomaterial-based delivery systems allow for the targeted, localised, and prolonged release of medications. Additionally, they are being investigated more and more for the purpose of controlling the interface between the host tissue and implanted biomedical materials. This review discusses innovative nanoparticle designs for precision and non-personalised applications to improve precision therapies. We prioritised nanoparticle design trends that address heterogeneous delivery barriers, because we believe intelligent nanoparticle design can improve patient outcomes by enabling precision designs and improving general delivery efficacy. We additionally reviewed the most recent literature on biomaterials used in biotherapy and vaccine development, covering drug delivery, stem cell therapy, gene therapy, and other similar fields; we have also addressed the difficulties and future potential of biomaterial-assisted biotherapies.